1986
DOI: 10.1111/1467-9566.ep11346455
|View full text |Cite
|
Sign up to set email alerts
|

Being epileptic: coming to terms with stigma

Abstract: Most commentators on the stigma assodated with epilepsy have assumed that the psycho-social distress sufferers experience derives wholly or largely from the discriminatory attitudes and behaviour of normal people. This 'orthodox viewpoint' is assessed and found to be lacking in empirical support. A study of the impact of epilepsy upon the lives of sufferers is reported, special attention being paid to coping strategies developed in the family and at work. A distinction between 'enacted' and 'felt' stigma is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
406
0
16

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 609 publications
(451 citation statements)
references
References 12 publications
17
406
0
16
Order By: Relevance
“…Individuals with cystic fibrosis (CF) reported hiding their condition during childhood in order to fit in socially (Christian and D'Auria 1997), while adults with severe signs and symptoms of CF were more likely to share their diagnosis than mildly affected adults who appeared Bhealthy^ (Lowton 2004;Modi et al 2010). The influence of physical appearance associated with illness has also been observed with conditions such as epilepsy and AIDS (Scambler and Hopkins 1986;Mansergh et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with cystic fibrosis (CF) reported hiding their condition during childhood in order to fit in socially (Christian and D'Auria 1997), while adults with severe signs and symptoms of CF were more likely to share their diagnosis than mildly affected adults who appeared Bhealthy^ (Lowton 2004;Modi et al 2010). The influence of physical appearance associated with illness has also been observed with conditions such as epilepsy and AIDS (Scambler and Hopkins 1986;Mansergh et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that up to 25% of people with LD are unknown to statutory agencies until later in life when the parent becomes too frail to care for the individual. 17 Prejudice, assumptions and negative stereotyping have led to attitudinal discrimination (or 'enacted stigma' 18 ) by medical services towards individuals with disabilities. 19 'Felt stigma', the shame of being disabled or of having a child with disabilities and the fear of being discriminated against, has been shown to be even more disruptive of peoples' lives and well-being than the actual discrimination experienced.…”
Section: Introductionmentioning
confidence: 99%
“…19 'Felt stigma', the shame of being disabled or of having a child with disabilities and the fear of being discriminated against, has been shown to be even more disruptive of peoples' lives and well-being than the actual discrimination experienced. 18 Studies investigating the oral health needs of people with LD indicate that they consistently have worse oral hygiene levels and a greater incidence of gingival inflammation and periodontal disease than that of the general population; yet they experience more untreated disease and more extractions. [20][21][22][23] However, a recent study demonstrated a better clinical status for adults with LD than the general population although they had fewer teeth indicating that treatment is more likely to involve extraction of teeth.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with the situation in the urban settings, where the anonymous nature of the interpersonal interactions makes the possibility of selective disclosure of one's stigmatized condition more practicable [59]. Scambler & Hopkins (1989) described the selective use of avoidance, reticence, and "guarded disclosure" as coping strategies for enacted stigma [15].…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of stigmatization among persons with epilepsy is about 50% in the developed countries [1] [14]. To cope with this prejudice and social rejection, individuals with epilepsy tend to maintain secrecy about their condition, and rarely make reference to it in the course of social interactions [15].…”
Section: Introductionmentioning
confidence: 99%